Tinjauan Hukum Islam terhadap Pelaksanaan Jual Beli Buah di Jorong Talago Laweh Nagari Sulit Air Solok Sumatera Barat - Umar, Zukarnaini; Mukharrom, Miftakhul; Putri, Lidiya (Al Barakat, 2025)
The implementation of fruit sales in Jorong Talago Laweh, Nagari Sulit Air, Solok, West Sumatra, uses a weight cutting system, price rounding, ijon (forward sale), or bulk purchase system. In the weight cutting system, there is a reduction of 5% to 30% for every weighing of 100 kg by the buyer. This study employs observational research through surveys, collecting data directly from the population/respondents by conducting interviews and distributing questionnaires as data collection tools. After collecting the data, it is processed to draw conclusions using inductive methods. This study is descriptive, explaining in clear and detailed sentences. The implementation of fruit sales in Jorong Talago Laweh, Nagari Sulit Air, Solok, West Sumatra, constitutes a form of sale that is not permissible and is invalid under the ijon system. The weight cutting of the fruit is deemed detrimental to one party. The implementation of fruit sales in Jorong Talago Laweh, Nagari Sulit Air, Solok, West Sumatra, using the ijon (bulk) system and weight cutting contains elements of gharar (uncertainty) and involves a fasid (invalid) contract, as it contradicts the ethical principles of buying and selling in Islam. It also represents a high-risk business practice, as stipulated in Article 8, Paragraph (3) of Law Number 2 of 1960 on Profit-Sharing Agreements, which states: “Payments by anyone, including owners and cultivators, to cultivators or owners in any form that includes ijon elements are prohibited.” Furthermore, the practice occurring in fruit sales transactions with the ijon system in Jorong Talago Laweh, Nagari Sulit Air, does not align with the principles of maslahah (public interest) due to its lack of benefits in the ijon trading activities.